A helical perylene diimide-based acceptor for non-fullerene organic solar cells: synthesis, morphology and exciton dynamics. Issue 5 (2nd May 2018) - Chen, Li; Wu, Mingliang; Shao, Guangwei; Hu, Jiahua; He, Guiying; Bu, Tongle; Yi, Jian-Peng; Xia, Jianlong
Abstract : Helical perylene diimide-based (hPDI) acceptors have been established as one of the most promising candidates for non-fullerene organic solar cells (OSCs). In this work, we report a novel hPDI-based molecule, hPDI2 -CN2, as an electron acceptor for OSCs. Combining the hPDI2 -CN2 with a low-bandgap polymeric donor (PTB7-Th), the blending film morphology exhibited high sensitivity to various treatments (such as thermal annealing and addition of solvent additives), as evidenced by atomic force microscope studies. The power conversion efficiency (PCE) was improved from 1.42% (as-cast device) to 2.76% after thermal annealing, and a PCE of 3.25% was achieved by further addition of 1, 8-diiodooctane (DIO). Femtosecond transient absorption (TA) spectroscopy studies revealed that the improved thin-film morphology was highly beneficial for the charge carrier transport and collection. And a combination of fast exciton diffusion rate and the lowest recombination rate contributed to the best performance of the DIO-treated device. This result further suggests that the molecular conformation needs to be taken into account in the design of perylene diimide-based acceptors for OSCs.